Pencegahan Stunting Pada Anak Melalui E-Booklet Pada Orang Tua di TK Aisyiyah Bustanul Athfal Kebasen - Atika Dhiah Anggraeni; Wahyu Riyaningrum (JPS : Jurnal Pengabdian Serulingmas, 2022)
Stunting is a nutritional problem related to the growth and development of toddlers caused by lack of nutritional intake for a long time because the feeding is not appropriate or balanced with the nutritional needs of children. Various efforts are made to prevent stunting, one of which is by health education using e-booklets. The target of the activity was the parents of students at Aisyiyah Bustanul Athfal Kindergarten with a total of 45 parents. Activities are carried out by providing material and pretesting postest. The results of activities obtained parental knowledge increased (85%). Similar efforts can be made to different respondents so that they can support stunting prevention programs and have a healthy generation.